Healthcare Access - Agrawal, Amit; Kosgi, Srinivas (IntechOpen, 2022)
Adequate healthcare access not only requires the availability of comprehensive healthcare facilities but also affordability and knowledge of the availability of these services. As an extended responsibility, healthcare providers can create mechanisms to facilitate subjective decision-making in accessing the right kind of healthcare services as well various options to support financial needs to bear healthcare-related expenses while seeking health and fulfilling the healthcare needs of the population. This volume brings together experiences and opinions from global leaders to develop affordable, sustainable, and uniformly available options to access healthcare services.